Hubungan Karakteristik Kepala Keluarga dengan Kepemilikan Jamban Keluarga di Kelurahan Bener, Kecamatan Tegalrejo, Kota Yogyakarta - Icah Febriwanti; Haryono Haryono; Surahma Asri Mulasari (Poltekkes Kemenkes Yogyakarta, 2010)
Family latrine is a facility attached to ahouse which is used to collect human faeces. The possession of this basic sanitation infrastructrure is important for reducing the incidence of diarrhoea. The objective of this study is to reveal the relationship between characteristics of household head live at Bener Village of Tegalrejo, Yogyakarta City, with the existence of family latrine in their houses. The study was a case control research, where the cases were 30 houses with family latrine, and the control group consisted of 30 houses without the facility.The results show that knowledge level (OR: 16,8; 95% CI: 2,0-40,9; p value<0,001), type of occupation (OR: 8,8; 95% CI: 1,0-77,0; p value<0,023), income level (OR: 7,3; 95% CI: 0,8-64,5; p value<0,044), and family burden (OR: 0,4; 95% CI: 0,1-0,9, p value<0,037) correlate with the ownership of the latrine; meanwhile educational level does not (OR: 1,6, 95% CI: 0,5-4,5; p value=0,417). The following logistic regression shows that knowledge level of family head is the strongest factor.